2022
DOI: 10.1186/s40249-022-00990-0
|View full text |Cite
|
Sign up to set email alerts
|

Armigeres subalbatus is a potential vector for Zika virus but not dengue virus

Abstract: Background Zika virus (ZIKV) and dengue virus (DENV) are closely related flaviviruses primarily transmitted by Aedes mosquitoes. Armigeres subalbatus is an emerging and widely distributed mosquito, and ZIKV has been detected and isolated from it. However, it is not clear whether Ar. subalbatus could be a vector for ZIKV and DENV or not. In this study, we investigated the infection and transmission of Ar. subalbatus to ZIKV and DENV. Methods A line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…This species was also present across the different sites independently of the season. Armigeres subalbatus , which was present in almost all sites, is a potential vector of ZIKV [ 69 ] and is implicated in the transmission of filaria [ 70 ]. Aedes vexans, Cx.…”
Section: Discussionmentioning
confidence: 99%
“…This species was also present across the different sites independently of the season. Armigeres subalbatus , which was present in almost all sites, is a potential vector of ZIKV [ 69 ] and is implicated in the transmission of filaria [ 70 ]. Aedes vexans, Cx.…”
Section: Discussionmentioning
confidence: 99%
“…A study of vector competence for ZIKV in China indicated that A. aegypti had the highest transmissibility, followed by A. albopictus , whereas C. quinquefasciatus had no transmission ability ( 43 ). Another study conducted in China indicated that A. subalbatus was a potential vector for ZIKV ( 44 ). All the above-mentioned studies suggested that there might be restricted autochthonous ZIKV transmission in Southern China, but further research was needed.…”
Section: Discussionmentioning
confidence: 99%
“…Vector susceptibility of Ae. albopictus to DENV-2 was evaluated by calculating the midgut infection rate (MIR; the number of infected midguts/the number of tested midguts), dissemination rate (DR; the number of infected ovaries/the number of infected midguts), and salivary gland infection rate (SGIR; the number of infected salivary glands/the number of tested mosquitoes) [ 31 , 32 ]. Genome copies of AaeDV were quantified in all midguts, ovaries, and salivary gland and genome copies were further determined in DENV2-positive tissues by absolute qRT-PCR.…”
Section: Methodsmentioning
confidence: 99%